Niat Dan Motivasi Dalam Kepemimpinan Pendidikan Islam - Ali Yakub (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2022)
This paper examines the role of intention and motivation in Islamic education leadership. The intention is an important thing in doing all actions because all actions or steps that we will take are very dependent on intentions. Even in Islam, the intention is very urgent and is often used as a pillar in a job or act of worship. The role of intention in initiating action will have a major influence on a person's motivation in carrying out an act or work.Motivation is a force that pushes people to do an action or behavior. The presence or absence of motivation in a person can be observed from the observation of his behavior. When we are excited to do a job, of course, we can argue that the person has high motivation and vice versa if we see someone doing the job not enthusiastic, we can judge that the person has low motivation.Leadership is defined as an activity to influence people who are directed towards organizational goals. One's leadership in an institution or place is strongly influenced by one's intentions and motivation when leading. Leaders who have good intentions will certainly carry out their leadership well and do not violate the rules set by religion or the state.Islamic education is a process of transinternalizing Islamic values ​​to students as a provision to achieve happiness and prosperity in the world and the hereafter. Islamic education is very influential for a person's path because the knowledge, experience a person has will affect the pattern of behavior and words he carries out every day.